Manifesto for the humanities : transforming doctoral education in good enough times - Smith, Sidonie (Digital humanities (Ann Arbor, Mich.), 2016)
"After a remarkable career in higher education, Sidonie Smith offers Manifesto for the Humanities as a reflective contribution to the current academic conversation over the place of the Humanities in the 21st century. Her focus is on doctoral education and opportunities she sees for its reform. Grounding this manifesto in background factors contributing to current "crises" in the humanities, Smith advocates for a 21st century doctoral education responsive to the changing ecology of humanistic scholarship and teaching. She elaborates a more expansive conceptualization of coursework and dissertation, a more robust, engaged public humanities, and a more diverse, collaborative, and networked sociality"--Back cover